Do current and former cigarette smokers have an attentional bias for e-cigarette cues?. (March 2018) - Lochbuehler, Kirsten; Wileyto, E Paul; Tang, Kathy Z; Mercincavage, Melissa; Cappella, Joseph N; Strasser, Andrew A
The similarity of e-cigarettes to tobacco cigarettes with regard to shape and usage raises the question of whether e-cigarette cues have the same incentive motivational properties as tobacco cigarette cues. The objective of the present study was to examine whether e-cigarette cues capture and hold smokers' and former smokers' attention and whether the attentional focus is associated with subsequent craving for tobacco cigarettes. It was also examined whether device type (cigalike or mod) moderated this relationship. Participants (46 current daily smokers, 38 former smokers, 48 non-smokers) were randomly assigned to a device type condition in which their eye-movements were assessed while completing a visual probe task. Craving was assessed before and after the task. Smokers, but not former or non-smokers, maintained their gaze longer on e-cigarette than on neutral pictures ( p = 0.004). No difference in dwell time was found between device type. None of the smoking status groups showed faster initial fixations or faster reaction times to e-cigarette compared with neutral cues. Baseline craving was associated with dwell time on e-cigarette cues ( p = 0.004). Longer dwell time on e-cigarette cues was associated with more favorable attitudes towards e-cigarettes. These findings indicate that e-cigarette cues may contribute to craving for tobacco cigarettes and suggest the potential regulation of e-cigarette marketing.